The Examining the Kerch Strait Bridge Attacks by The Prism of International Humanitarian Law - Sitompul, Ray Radjuman Janiver Giftson; Dewi, Tjokorda Istri Diah Widyantari Pradnya (Kertha Negara : Journal Ilmu Hukum, 2024)
The Kerch Strait Bridge, also known as The Crimean Bridge, is an infrastructure that stretches between the Kerch Peninsula of Crimea and the Taman Peninsula of Krasnodar Krai in Russia. This infrastructure has been destroyed as a result of the ongoing conflict between The Russian Federation and Ukraine. This article aimed to analyze whether the attacks was in accordance with the principle of International Humanitarian Law (IHL). This article relies on normative legal research and statutory, case, and fact approaches to analyze this matter. The study designated that the attack on the Kerch Strait Bridge followed the principles which is set in the International Humanitarian Law. Those said principles are the principle of distinction, the principle of military necessity, the principle of proportionality, and the principle of precautions.